Gombrowicz w Słowenii: ramy interpretacyjne czasu i przestrzeni kulturowej - Tokarz, Bożena (Przekłady Literatur Słowiańskich, 2012)
Gombrowicz in Slovenia: interpretational frames of time and cultural space The recontextualization of the prose by Gombrowicz occurred within three different interpretational frames in the translation into Slovene, time frames and space frames: in the 70., 90. and in 2000. They are appointed by the strategy of the translators, by the political situation, by the translations and the reception of foreign literature (above all western literature), by the global situation connected with culture and civilization and by the condition of the target literature of the translation. All of them are determined by the system of expectations of the audience and by the „life” of the translations. In the translations of Gombrowicz have evolved cultural barriers and the degree of crossing them from the side of the source culture and also from the side of the target culture: beginning with the political actualization of Polish awareness through its rhetorical over-coding up to hybridization and mutual merging of times, space, cognitive and emotional attitudes. The difficulty of following the intercultural literary dialogue in the Slovene prose is deepened by the fact that the translations of American literatures occurred more or less when the translations of Gombrowicz were done (particularly, beginning in the mid 80.). Key words: prose, Gombrowicz, translation, culture, intercultural communication.